OPTIMIZATION OF THE THERAPY OF ACUTE RESPIRATORY VIRAL INFECTIONS IN CHILDREN IN WEST-KAZAKHSTAN - A. N. Seipenova; K. B. Abdrahmanov (Детские инфекции (Москва))
The work presents the results of observation of the dynamics of the ARVI indicators in children of Aktobe city and the Aktyubisk region for the period of 2006— 2010, also ethnological structure and age composition of children. The authors also speak about clinical efficacy of combined application of Viferon preparation with differential choice of dozes and the duration of course of treatment for children with ARVI and recurrent disease.